Gene duplication to the Y chromosome in Trinidadian Guppies. Issue 6 (2nd February 2022) - Lin, Yuying; Darolti, Iulia; Furman, Benjamin L. S.; Almeida, Pedro; Sandkam, Benjamin A.; Breden, Felix; Wright, Alison E.; Mank, Judith E.
Abstract: Differences in allele frequencies at autosomal genes between males and females in a population can result from two scenarios. First, unresolved sexual conflict over survival can produce allelic differentiation between the sexes. However, given the substantial mortality costs required to produce allelic differences between males and females at each generation, it remains unclear how many loci within the genome experience significant sexual conflict over survival. Alternatively, recent studies have shown that similarity between autosomal and Y sequences can create perceived allelic differences between the sexes. However, Y duplications are most likely in species with large nonrecombining regions, in part because they simply represent larger targets for duplications. We assessed the genomes of 120 wild‐caught guppies, which experience extensive predation‐ and pathogen‐induced mortality and have a relatively small ancestral Y chromosome. We identified seven autosomal genes that show allelic differences between male and female adults. Five of these genes show clear evidence of whole or partial gene duplication between the Y chromosome and the autosomes. The remaining two genes show evidence of partial homology to the Y. Overall, our findings suggest that the guppy genome experiences a very low level of unresolved sexual conflict over survival, and instead the Y chromosome, despite its small ancestral size and recent origin, may nonetheless accumulate genes with male‐specific functions.